Pulmonary ligament rupture due to a bronchial artery aneurysm-induced hematoma: a case report - Yasuaki Tomioka; Eiji Yamada; Tsuyoshi Hyodo; Masahiko Muro (Surgical Case Reports)
Abstract Background Bronchial artery aneurysm (BAA) is a rare vascular anomaly with the potential for serious complications, such as rupture leading to hemothorax or hemoptysis. Although bronchial artery embolization (BAE) is recognized as an effective intervention for ruptured BAA, video-assisted thoracoscopic surgery (VATS) is a minimally invasive approach for the treatment of associated hemothorax. Case presentation A 73-year-old woman presented with a mediastinal hematoma from a ruptured BAA, causing bilateral hemothorax. Emergency angiography revealed a saccular BAA that was successfully embolized using a microcatheter and coil. Subsequent computed tomography revealed an expanding hemothorax managed by VATS, with 1400 mL of blood drained. During VATS, thoracoscopy revealed pulmonary ligament rupture, which was attributed to increased intramediastinal pressure. The patient was discharged eight days postoperatively with no complications. This case highlights the use of BAE and VATS in the management of mediastinal BAA rupture and massive hemothorax. Conclusions BAE proved to be an effective strategy for the management of ruptured mediastinal BAAs. VATS is a valuable standby procedure for hematoma removal, but the indication should be carefully determined because of the risk of BAA re-rupture.